Pengaruh Influencer dan Electronic Word of Mouth (e-WOM) Terhadap Keputusan Pembelian Bika Ambon Ahun di Kota Medan (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study aims to analyze the influence of influencers and electronic word of mouth (e-WOM) on the purchase decision of Bika Ambon Ahun in Medan City. The rapid development of social media has transformed how consumers obtain information and make purchasing decisions, making influencers and e-WOM essential components in shaping consumer perceptions and behavior. This research employs an associative quantitative method with data collected through questionnaires distributed to consumers who were familiar with the product through social media. The data were analyzed using partial (t-test) and simultaneous (F-test) analyses to examine the strength of the relationship between the independent variables and the purchase decision. The findings indicate that influencers have a positive and significant effect on purchase decisions, as consumers perceive influencer review content to be credible, engaging, and persuasive. Likewise, e-WOM demonstrates a positive and significant influence, supported by consumer trust in online reviews, comments, and recommendations that serve as strong social proof before making a purchase. Simultaneously, both influencers and e-WOM contribute 68.4% to the variation in purchase decisions, while the remaining 31.6% is influenced by other external factors. These results emphasize that the combined influence of influencers and e-WOM generates a synergistic effect that strengthens consumer interest, trust, and confidence in purchasing local products such as Bika Ambon Ahun. The study implies the importance for businesses to optimize digital marketing strategies by collaborating with credible influencers and encouraging positive online reviews as a means to reinforce consumer purchase decisions.